2023
DOI: 10.3389/fvets.2023.1093274
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and selenium nanoparticles have a synergistic protective effect during cryopreservation of bull semen

Abstract: IntroductionIn the present study, the synergistic protective effect of co-supplementation of glutathione (GSH) with selenium nanoparticles (SeNPs) on the cryopreservation efficiency of bull semen was analyzed.MethodsAfter collection, the ejaculates of Holstein bulls were subsequently diluted with a Tris extender buffer supplemented with different concentrations of SeNPs (0, 1, 2, and 4 μg/ml), followed by semen equilibration at 4°C and assessment of sperm viability and motility. Subsequently, the ejaculates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“… 80 Beginning with the discovery of GPx as the first mammalian selenoprotein in 1973, considerable achievements have been made in the past decades for elucidating the physiological roles of selenoenzymes or selenoproteins in the regulation of mammalian antioxidant defense systems by reducing tyrosyl radicals in proteins, degrading lipid hydroperoxides, scavenging free radicals, and preventing oxidative DNA damages and cell apoptosis. 80 , 81 These former literatures have also confirmed that these characterized selenoenzymes or selenoproteins induced by SeNPs effectively diminish the outcomes of disrupted inflammatory response cascades such as the increased expression of chemoattractant cytokines, adhesive molecules, fibrogenesis, collagens, and metalloproteinase by inhibiting the activation of nuclear factor-κB (NF-κB) or phosphorylation of NF-κB via redox related signaling pathways or macrophage signaling transduction pathways. 82 , 83 It is also of interest that the dramatic reductions in the inflammatory response cascades decompose the proliferation of fibroblasts and then benefit the anti-fibrosis, anti-inflammatory, and antioxidant properties of SeNPs.…”
Section: Discussionmentioning
confidence: 85%
“… 80 Beginning with the discovery of GPx as the first mammalian selenoprotein in 1973, considerable achievements have been made in the past decades for elucidating the physiological roles of selenoenzymes or selenoproteins in the regulation of mammalian antioxidant defense systems by reducing tyrosyl radicals in proteins, degrading lipid hydroperoxides, scavenging free radicals, and preventing oxidative DNA damages and cell apoptosis. 80 , 81 These former literatures have also confirmed that these characterized selenoenzymes or selenoproteins induced by SeNPs effectively diminish the outcomes of disrupted inflammatory response cascades such as the increased expression of chemoattractant cytokines, adhesive molecules, fibrogenesis, collagens, and metalloproteinase by inhibiting the activation of nuclear factor-κB (NF-κB) or phosphorylation of NF-κB via redox related signaling pathways or macrophage signaling transduction pathways. 82 , 83 It is also of interest that the dramatic reductions in the inflammatory response cascades decompose the proliferation of fibroblasts and then benefit the anti-fibrosis, anti-inflammatory, and antioxidant properties of SeNPs.…”
Section: Discussionmentioning
confidence: 85%
“…Another key step in IVF for both humans and animals is semen cryopreservation—a process that necessarily involves repeated freezing and thawing cycles, which manifests the production of damaging ROS and causes oxidative stress which together reduces sperm viability by more than 35% [ 84 ]. Under these conditions, studies have shown that SeNP supplementation markedly improves gamete quality during IVF procedures [ 83 , 85 ]. For example, bovine semen supplemented with 0.5 and, 1.0 μg/mL of SeNPs prior to cryopreservation recorded enhanced post-thawing sperm motility and membrane integrity with reduced DNA damage and importantly, a higher fertility rate than that of the control [ 70 ].…”
Section: Selenium Nanoparticlesmentioning
confidence: 99%
“…When combined with glutathione (GSH), SeNPs have also been shown to protect bull spermatozoa from cryoinjury, resulting in improved semen motility, mitochondrial activity, plasma membrane integrity, and acrosome integrity. The co-supplementation of GSH and SeNPs has also been found to enhance the antioxidant capacity and embryonic development potential of frozen-thawed bull spermatozoa 22 . Additionally, enriching semen extender with Se-NPs has been found to improve the post-thaw sperm quality of Holstein bulls and consequently increase the in vivo fertility rate by reducing apoptosis, lipid peroxidation, and sperm damage caused by cryopreservation 23 .…”
Section: Introductionmentioning
confidence: 98%